RHEUMATIC DISEASES AND ENDOTHELIAL FUNCTION - Varvara L. Мarchuk; Nickolai V. Sobotyuk; Sergei V. Bochantsev ("Paediatrician" Publishers LLC, 2018)
The review analyzes the role of chronic inflammatory diseases in the induction of endothelial dysfunction as a factor in the acceleration of atherosclerotic changes in the cardiovascular system. The importance of non-invasive techniques for evaluating endothelial dysfunction to detect preclinical atherosclerotic changes in children and adolescents with rheumatic was discussed. It is postulated that the detection of early signs of endothelial dysfunction in children and adolescents with rheumatic diseases, along with traditional risk factors, should become an integral part of the strategy for preventing adverse cardiovascular events in subsequent age periods.